Roles of Interactions Between Toll-Like Receptors and Their Endogenous Ligands in the Pathogenesis of Systemic Juvenile Idiopathic Arthritis and Adult-Onset Still’s Disease - Jung, Ju-Yang; Kim, Ji-Won; Suh, Chang-Hee; Kim, Hyoun-Ah (Frontiers in Immunology, 2020)
Systemic juvenile idiopathic arthritis (JIA) and adult-onset Still’s disease (AOSD) are systemic inflammatory disorders that manifest as high-spiking fever, joint pain, evanescent skin rash, and organomegaly. Their pathogenesis is unclear, but inflammation is triggered by activation of the innate immune system with aberrant production of proinflammatory cytokines. Along with extrinsic factors, intrinsic pathways can trigger an unexpected immune response. Damage-associated molecular patterns (DAMPs) induce the activation of innate immune cells, leading to sterile inflammation in systemic JIA and AOSD. These endogenous proteins interact with Toll-like receptors (TLRs), which are pattern recognition receptors, and mediate immune signaling following stimulation by pathogen-associated molecular patterns and DAMPs. Several DAMPs, such as S100 proteins, play a role in the development or severity of systemic JIA and AOSD, in which their interactions with TLRs are altered. Also, the expression levels of genes encoding DAMPs contribute to the susceptibility to systemic JIA and AOSD. Herein, we review reports that TLR and DAMP signaling initiates and/or maintains the inflammatory response in systemic JIA and AOSD, and their correlations with the clinical characteristics of those diseases. In addition, we assess their utility as biomarkers or therapeutics for systemic JIA and AOSD.